Balance Control in Patients with Subacute Non-Specific Low Back Pain, with and without Lumbar Instability: A Cross-Sectional Study - Hlaing, Su Su (J Pain Res, 2020)
BACKGROUND: Patients with low back pain (LBP) have poorly coordinated neuromuscular control, which may alter the normal postural stability of the spine. Altered movement control may occur at any stage of LBP. PURPOSE: (1) To identify differences in balance control and proprioceptive sense between subacute non-specific LBP (NSLBP) patients with and without lumbar instability (LI) and healthy subjects and (2) to investigate the correlation between factors of motor control deficits and balance. PATIENTS AND METHODS: Thirty-six participants matched by gender, age, and body mass index (BMI) were allocated into three groups of 12: subacute NSLBP patients with LI, subacute NSLBP patients without LI, and healthy subjects. Balance, proprioceptive sense, pain, functional disability, and fear of movement were evaluated. RESULTS: Subacute NSLBP patients with LI exhibited greater impairments in balance control, proprioceptive sense, and functional ability than patients without LI (p<0.05). Subacute NSLBP patients showed more impairments in balance control, proprioceptive sense, and fear of movement than healthy subjects (p<0.001), with the following effect sizes (partial η(2)) for static balance on stable and unstable surface: 0.597 and 0.560, anticipatory balance: 0.417, and dynamic balance: 0.536; proprioceptive sense: 0.676; and fear of movement: 0.379. Significant fair correlations were found between (1) static balance and proprioceptive sense, functional disability, and fear of movement; (2) ﻿functional ﻿reach ﻿test (FRT) and pain; and (3) the ﻿five ﻿times ﻿sit to ﻿stand ﻿test (FTSTS) and functional disability. CONCLUSION: Subacute NSLBP patients with LI showed greater impairment in balance control than patients without LI. Reduced proprioceptive sense, increased pain, functional disability, and fear of movement were fairly related to impaired balance.